Design and development of AC motor speed controlling system using touch screen with over heat protection - Rani, Prathipati Ratna Sudha; Eragamreddy, Gouthami; Inthiyaz, Syed; Ravikanth, Sivangi; Najumunnisa, Mohammad; Rajanna, Bodapati Venkata; Kumar, Cheeli Ashok; Ahammad, Shaik Hasane (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Design and implementation of an AC motor speed control and monitoring system based on a touch screen interface with built-in overheat protection, utilizing Arduino, meets the increasing demand for efficient, user-friendly motor control in many industrial applications. This system offers an easy-to-use interface to manage the speed of an AC motor, with real-time feedback and adjustments through a touch screen display. The system employs an Arduino microcontroller, which accepts inputs from the touch screen and processes these to regulate the motor's speed through a pulse width modulation (PWM) method. The system also has an overheat protection system, which it is able to monitor the temperature of the motor via a temperature sensor. When the motor reaches a predetermined temperature, the system automatically shuts off power to avoid damage. The intuitive touch screen facilitates convenient monitoring of motor parameters like temperature, giving a smooth experience to operators. The modular design of the system provides scalability across applications, ranging from household appliances to large industrial systems, with reliability, energy efficiency, and safety in motor-driven processes.